ON HARNESSING NATURAL RESOURCES FOR SUSTAINABLE DEVELOPMENT - MISHRA, Sudhanshu K. (Journal of Environmental Management and Tourism; Vol 1 No 1 (2010): JEMT Volume I Issue 1(1) Summer 2010, 2010)
There is now abundant scientific evidence that humanity is living unsustainably. The environment is gradually becoming more overstressed. People now are transforming ecosystems throughout the world at a faster and more extensive pace than any other time in human history. We are culturally given to the wasteful use of resources. In this milieu, this paper observes that bringing human use of natural resources within sustainable limits will require a major collective effort. There is a need to sensitize the people, to change their mindset and the worldview, and to direct their efforts to a serious thinking and action to change our present preoccupation with an unsustainable development towards sustainable development. It highlights the role of the ‘creative core’ and good governance. But the intelligentsia, especially in the less developed nations where social consciousness is dominated by the myopic personal agenda, will not be effective unless the monitoring of the entire program of development is efficient. The people must, therefore, come forward. But, while social consciousness is weak and dormant, this requirement pushes us into the vicious circle. This vicious circle is the real trap and obstacle to sustainable development.